Peran Riset Dalam Perwujudan Desain - -, Sunarmi (Institut Seni Indoensia Surakarta, 2013)
This paper is to discuss the results of a literature study on the role of research inthe design embodiment . The design has an important role in the formation of thehuman character , can pattern the design of the human mind at work as one of habit .Correspondence between the design of the user is the highest degree on the success ofthe design , the design is good . There are several stages in one embodiment is aresearch design . Research conducted to determine the design work on the designobject . In order to do proper research needs to be an understanding of designobjectives and benefits of the research design . What are the element that must beconsidered in the research design , in order to obtain work on the design of appropriateobjects . To answer these problems need to be addressed on the research design in thedesign process .The results of the research study design required in the design process at every stage .At the formulation stage of the research design required design . Target research toformulation design is ( 1 ) Potential Areas , ( 2 ) The level of competition , ( 3 )Consumer Dynamics , ( 4 ) Opportunity Design , ( 5 ) development of technology . Fouraspects are the basis for the formulation of feasibility or design work on the object .These data can be obtained from various sources including: literature , informants , andsocial facts or data field . The selection of literature on the eligibility or qualificationdidasarakan author and recency literature . Informants were selected based on relevantqualifications in accordance with the purposes of information . Selected for each socialfacts based on relevant qualifications .